A novel structure luminous flexible fiber was prepared via aerosol jet printing - Keke Wang; Zhi Liu; Chenxin Zhou; Baixiong Liu; Feng Gu; Shixian Xiong; Jianfeng Liu; Munan Yang (Scientific Reports)
Abstract Utilizing aerosol jet printing (AJP), this study achieves a breakthrough in fabricating luminescent fibers with superior optical performance and flexibility. The Y2O3:Eu3+ coated high silica glass fibers demonstrate luminous efficiency twice that of traditional methods, retaining 80% after 250 bending cycles and 90% after sweat immersion. This AJP technique not only elevates the potential of smart fabrics but also represents a significant innovation in lighting technology, providing new ideas for advanced functional fiber fabrication.